Computational models and tools. Issue 11 (13th November 2018) - Schuemann, Jan; Bassler, Niels; Inaniwa, Taku
Abstract : In this chapter, we describe two different methods, analytical (pencil beam) algorithms and Monte Carlo simulations, used to obtain the intended dose distributions in patients and evaluate their strengths and shortcomings. We discuss the difference between the prescribed physical dose and the biologically effective dose, the relative biological effectiveness (RBE) between ions and photons and the dependence of RBE on the linear energy transfer (LET). Lastly, we show how LET‐ or RBE‐based optimization can be used to improve treatment plans and explore how the availability of multimodality ion beam facilities can be used to design a tumor‐specific optimal treatment.